Designing with objects object-oriented design patterns explained with stories from Harry Potter - Kak, Avinash C. (John Wiley & Sons, 2015)
" All code examples in the book are available for download on a companion site with resources for readers and instructors. A refreshing alternative to the rather abstract and dry explanations of the object-oriented design patterns in much of the existing literature on the subject In 24 chapters, Designing with Objects explains well-known design patterns by relating them to stories from the Harry Potter series"-- Provided by publisher.